The Expression of Defensin-Associated Genes May Be Correlated With Lymph Node Metastasis of Early-Stage Tongue Cancer - Doh Young Lee; J. Hun Hah; Woo-Jin Jeong; Eun-Jae Chung; Tack-Kyun Kwon; Soon-Hyun Ahn; Myung-Whun Sung; Seong Keun Kwon (Clinical and Experimental Otorhinolaryngology, 2022)
Objectives. We aimed to assess the genetic differences between cases of early-stage tongue cancer that were positive or negative for lymph node metastasis. Methods. In total, 35 cases of tongue cancer with RNA sequencing data were enrolled in this study. The gene expression profile of the following two groups was compared: N0 group (T stage 1 or 2 with N0 stage) and N+ group (T stage 1 or 2 with N+ stage). Using the R and limma packages in the Bioconductor program, we extracted the differentially expressed genes (DEGs). Gene ontology and pathway enrichment analysis were performed using the Database for Annotation, Visualization and Integration Discovery (DAVID) online tool. Immune cell infiltration was analyzed using the CIBERSORT online program. Immunochemical staining of the cancer tissue was evaluated and The Cancer Genome Atlas (TCGA) data were analyzed to validate the identified DEGs. Results. No significant differences were found in the infiltration of 22 types of immune cells. Among a total of 51 identified DEGs, 14 genes were significantly upregulated, while 37 genes were significantly downregulated (P<0.01; fold change >2). Pathway analysis revealed significant associations with the arachidonic acid metabolism-related pathway, calcium signaling, and the muscle contraction pathway. The following DEGs were the most significantly different between the two groups: DEFB4A, SPRR2B, DEFB103B, SPRR2G, DEFB4B, and FAM25A. TCGA data showed that DEFB4A and DEFB103B were more highly expressed in the N0 group than in the N+ group, although the difference did not achieve statistical significance. Immunochemical staining of cancer tissue revealed significantly higher expression of defensin in the N0 group. Conclusions. Defensin (DEFB4A, DEFB103B, DEFB4B) may be a novel biomarker for early regional metastasis in T1/2 tongue cancer.